Vulnerability in Scandinavian Art and Culture - Adriana Margareta Dancus, Mats Hyvönen, Maria Karlsson (Engaging Vulnerability, 2020)
In this open access book, seventeen scholars discuss how contemporary Scandinavian art and media have become important arenas to articulate and stage various forms of vulnerability in the Scandinavian welfare states. How do discourses of privilege and vulnerability coexist and interact in Scandinavia? How do the Scandinavian countries respond to vulnerability given increased migration? How is vulnerability distributed in terms of margin and centre, normality and deviance? And how can vulnerability be used to move audiences towards each other and accomplish change? We address these questions in an interdisciplinary study that brings examples from celebrated and provocative fiction and documentary films, TV-series, reality TV, art installations, design, literature, graphic art, radio podcasts and campaigns on social media.